2019
DOI: 10.1038/s41433-019-0340-3
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus (rapamycin) for the targeted treatment of the fibrotic sequelae of Graves’ orbitopathy

Abstract: Background Rapamycin (alternatively known as sirolimus) is a macrolide immunosuppressant commonly used for organ transplantation. It acts both on lymphocytes through the mechanistic target of rapamycin (mTOR) pathway to reduce their sensitivity to interleukin-2 (IL-2) and, importantly, also has anti-fibrotic properties by acting on myofibroblasts. The latter have been implicated in the pathogenesis of thyroid eye disease (TED). Aim To describe successful treatment and reversal of extraocular muscle fibrosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
1
19
0
2
Order By: Relevance
“…The fact that they may not be widely available or affordable, as well as the lack of information, say, on the need of subsequent rehabilitative surgery, further add to their current limitations. As multiple pathogenic pathways are implicated in GO, several targeted therapies are worth exploring in clinical trials, e.g., monoclonal antibodies and/or small molecules targeting the TSHR (187,188) or the CD40 molecule expressed in both thyrocytes and orbital fibroblasts (189), or anti-IL-23/anti-IL-17 for the IL-23/IL-17 axis and sirolimus for the mTOR pathway (190). Worthwhile is also a modulating impact on the microbiome in patients with GO (191).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that they may not be widely available or affordable, as well as the lack of information, say, on the need of subsequent rehabilitative surgery, further add to their current limitations. As multiple pathogenic pathways are implicated in GO, several targeted therapies are worth exploring in clinical trials, e.g., monoclonal antibodies and/or small molecules targeting the TSHR (187,188) or the CD40 molecule expressed in both thyrocytes and orbital fibroblasts (189), or anti-IL-23/anti-IL-17 for the IL-23/IL-17 axis and sirolimus for the mTOR pathway (190). Worthwhile is also a modulating impact on the microbiome in patients with GO (191).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown an improvement in patients affected by fibrotic sequelae of Graves orbitopathy, or thyroid eye disease (TED), and the reversal of extraocular muscle fibrosis if treated with sirolimus (rapamycin). This drug has been shown to exert its anti-fibrotic activity by acting on myofibroblasts, the primary ECM-secreting cells during wound healing and fibrosis ( Roos and Murthy, 2019 ). Furthermore, glaucoma filtration surgery (GFS) is the most commonly used surgical procedure for glaucoma treatment but postoperative fibrosis is still a major threat for the success of this treatment.…”
Section: Organ Fibrosis Emt and Possible Anti-emt Therapeutic Stratementioning
confidence: 99%
“…The fact that they may not be widely available or affordable further adds to their limitations. As multiple pathogenic pathways are implicated in GO, several targeted therapies are worth exploring in clinical trials (e.g., anti-IL-23 or anti-IL-17 for the IL-23/IL-17 axis; sirolimus for the mTOR pathway [45,101,102]). However, the process of developing and evaluating novel therapeutic agents is usually time-consuming and costly.…”
Section: Discussionmentioning
confidence: 99%